Sintesis basa schiff dari Vanilin dan p-Toluidina - Fauzan, Muhammad Akmal (Maliki Interdisciplinary Journal, 2024)
Schiff's base is a compound formed from condensation reaction of a carbonyl compound with a primary amine. The characteristic of Schiff base compounds is the imine group. Schiff's base has benefits as an antifungal, antioxidant, and antibacterial. The research method is the synthesis of Schiff base from vanillin and p-toluidine, testing the melting point of the Schiff base compound, solubility test with 2M NaOH and distilled water, characterization using an FTIR spectrophotometer, GC-MS, 1H-NMR . The product obtained is (E)-2-methoxy-4-((p-tolylimino)methyl)phenol, yellow in color, mass of 0.9158 g, percent yield of 95%, boiling point of 114-117 oC, soluble in 2M NaOH and insoluble in water. Analysis using GC-MS resulted in a retention time of 4.379 minutes with an area of ​​1056549 and a percent area of ​​75.68% with molecular mass is 241 g/mol. Analysis using 1H-NMR resulted in a chemical shift of 7.52 ppm (imine group). Characterization of the synthesized product using a 1H-NMR spectrophotometer showed that there were nine signals obtained with 15 protons. Analysis using FTIR showed that there was absorption at 1690-1640 cm-1 which was the absorption of C=N stretch from the imine group.